Analyzing the role of quality governance in green initiatives and the impact towards the organisational performance / Zuhairah Hasan and Noor Azman Ali - Hasan, Zuhairah; Ali, Noor Azman (UiTM Cawangan Johor, 2019)
This article presents an analysis of quality governance as an intervening role between the green initiatives implemented by the ISO 14001 EMS firms in Malaysia and the performance of the organisations. Previous research points at the importance of green marketing is expanding and many companies are embracing new strategies. The study aims to investigate the impact of green initiatives on the organisational performance and the quality governance as a moderating factor between the green initiatives and the organisational performance. The current research will include green product, green price, green promotion, green distribution, top management, shared vision and financial resources as a green initiative. A total of 150 responses was collected using simple random sampling technique. This study employs partial least square-structural equation modelling (PLS-SEM) as the main statistical technique. The findings reveal that green product, green pricing, top management, shared vision and financial resources significantly positively affects organizational performance. Management implications for the implementation of green initiatives and marketing are discussed.